Application of Historical Burn Analysis Method in Determining Agricultural Premium Based on Climate Index Using Black Scholes Method - Ariyanti, Devi; Riaman, Riaman; Irianingsih, Iin (Universitas Muhammadiyah Mataram, 2020)
Farmers often suffer losses due to crop failure. The failure of the harvest is influenced by one of them is flooding, especially in Bandung which is quite frequent rain. Therefore one of the government's efforts to minimize losses from crop failures is the existence of an agricultural insurance program. The insurance system used is climate index insurance where the climate index is not plant insurance. This study aims to get a large premium to be paid by farmers using the Black-Scholes method. Meanwhile, to determine the climate index using the Historical Burn Analysis method. The results of this study are getting a variety of trigger values and exit values as well as the amount of premium that must be paid by farmers every planting season. Trigger values represent the minimum full payment limit. The exit value represents the maximum limit for no payment. The premium value obtained based on the selected trigger value also varies and is large enough so that it can be considered by farmers in choosing an agricultural insurance policy. Therefore, the method used must still be investigated to adjust to farmers, especially in Bandung.